Brain stem death. Issue 10 (October 2018) - Cowan, Richard; Miles, Barbara
Abstract: The concept of brain and brain stem death developed from the observation of apnoeic comatose patients. In the UK, the diagnosis of brain stem death is made by clinically testing brain stem function once specific preconditions have been met. The exact definition of brain death and some details regarding the tests required to make this diagnosis vary across the globe. However, the majority of tests carried out are similar to those in the UK. In this review we define brain stem death and the clinical tests used to confirm it. The use of ancillary testing can have a role in patients where clinical tests are not possible and this is also discussed.